Activation of transforming growth factor-β signaling by SUMO-1 modification of tumor suppressor Smad4/DPC4 - Lin, Xia; Liang, Min; Liang, Yao-Yun; Brunicardi, F. Charles; Melchior, Frauke; Feng, Xin-Hua (The journal of biological chemistry, 2003)
Smads are important intracellular effectors in signaling pathways of the transforming growth factor-β (TGF-β) superfamily. Upon activation by TGF-β, receptor-phosphorylated Smads form a complex with tumor suppressor Smad4/DPC4, and the Smad complexes then are imported into the nucleus. Although diverse pathways regulate the activity and expression of receptor-phosphorylated and inhibitory Smads, cellular factors modulating the activity of the common Smad4 remain unidentified. Here we describe the involvement of the small ubiquitin-like modifier-1 (SUMO-1) conjugation pathway in regulating the growth inhibitory and transcriptional responses of Smad4. The MH1 domain of Smad4 was shown to associate physically with Ubc9, the ubiquitin carrier protein (E2) conjugating enzyme in sumoylation. In cultured cells, Smad4 is modified by SUMO-1 at the endogenous level. The sumoylation sites were identified as two evolutionarily conserved lysine residues, Lys-113 and Lys-159, in the MH1 domain. We found that the mutations at Lys-113 and Lys-159 did not alter the ability of Smad4 to form a complex with Smad2 and FAST on the Mix.2 promoter. Importantly, SUMO-1 overexpression enhanced TGF-β-induced transcriptional responses. These findings identify sumoylation as a unique mechanism to modulate Smad4-dependent cellular responses.
Gesehen am 05.09.2023